2004
DOI: 10.1007/bf03030557
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various pretreatments on seed germination ofCalystegia soldanella (Convolvulaceae), a coastal sand dune plant

Abstract: We tested various pretreatments to enhance the germination of 'Sea bells' (Calystegia soldanella Roem. et Schult).One experiment, which improved the germination rate by 70%, involved first scarifying the seed coats, then immersing the seeds in 50 ppm GA3 for 24 h. A GA3-alone pretreatment did not increase germination. However, the most effective method, with a 100% success rate, included 3 h of acid pretreatment with 98% H2SO4. We also used scan. ning electron microscopy (SEM) to examine the seed-coat surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Conversely, of the nine species with a preference for the highest germination temperature (30/20 C), seven are beach plants. Two of the shifting dune species which we did not include in the niche analyses due to their low germinability (Calystegia soldanella and Eryngium maritimum) have also been reported to germinate with summer temperatures (Walmsley and Davy, 1997;Ko et al, 2004;Di Sacco and Bedini, 2015). The estimated best temperature for germination in cliffs is one degree above winter day temperatures, while in beaches it corresponds to average summer day temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, of the nine species with a preference for the highest germination temperature (30/20 C), seven are beach plants. Two of the shifting dune species which we did not include in the niche analyses due to their low germinability (Calystegia soldanella and Eryngium maritimum) have also been reported to germinate with summer temperatures (Walmsley and Davy, 1997;Ko et al, 2004;Di Sacco and Bedini, 2015). The estimated best temperature for germination in cliffs is one degree above winter day temperatures, while in beaches it corresponds to average summer day temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…After collection, seeds spent 3 weeks in the laboratory (21 C, 50 % relative humidity) before seed cleaning and the start of the germination experiments. Because physical seed dormancy was expected in Calystegia soldanella (Ko et al, 2004) and Lavatera arborea (Santo et al, 2015), seeds of these two species were mechanically scarified before further manipulation.…”
Section: Seed Germination Experimentsmentioning
confidence: 99%
“…Studies on Merremia species (Sharma and Sen, 1975;Azania et al, 2003), Calystegia soldanella (Kondo et al, 2001(Kondo et al, , 2002Ko et al, 2004), Convolvulus spp. (Brown and Porter, 1942;Koller and Cohen, 1959;Weaver and Riley, 1982;Tamak et al, 1994;Gonzalez-Martin, 1998) and Jacquemontia spp.…”
Section: Discussionmentioning
confidence: 99%
“…ornamental species of Ipomoea (Hardcastle, 1978; Horak and Wax, 1991; Ogunwenmo, 2006) and Merremia (Azania et al , 2003) and the weedy species Ipomoea spp. (Misra, 1963; Chandler et al , 1977; Norsworthy and Oliveira, 2007), Convolvulus arvensis (Brown and Porter, 1942; Weaver and Riley, 1982; Tamak et al , 1994), Calystegia soldanella (Kondo et al , 2000; Ko et al , 2004), Evolvulus alsinoides (Saharan et al , 2001) and Cuscuta campestris (Hutchison and Ashton, 1980; Benvenuti et al , 2005). In their review of the biology and control of weedy Ipomoea spp., Elmore et al (1990) suggested that seeds of morningglory species are dormant due to a water-impermeable seed coat, and they reported that most of them require high temperatures to germinate.…”
Section: Introductionmentioning
confidence: 99%
“…soldanella's seeds and the species is acknowledged as an important fore-dune species, which is able to trap sand to a certain extent (Ko et al 2004).…”
Section: Aims and Research Questionsmentioning
confidence: 99%